In medias res: Marshall Mcluhan and the otherness of his “theory” - Sodeika, Tomas (Religija ir kultūra, 2009)
Marshall McLuhan, again and again referred to as a “guru” of media culture, is perhaps best known for his aphorism The Medium is the Message. McLuhan’s contribution to the field of communication study was highly praised in popular culture but in academic spheres being received as doubtful. His basic idea is that the message is very much influenced by the medium of delivery. One would recognize this position as the definitive media determinism. McLuhan however emphasize the humanistic character of his “theory”. McLuhan’s manner of theorizing is other than traditional. McLuhan is a master of aphorisms, incredible pronouncements, humorous quips, and wordplay.